Comparação da administração ad libitum de dietas “very low fat” e cetogênica em camundongos e os reflexos fisiológicos da não adesão - Silva, Clédia Silveira Flores da (2024)
Obesity poses a significant threat to public health, as it increases the risk of chronic non-communicable diseases, negatively impacting quality of life and work productivity, and generating high costs for the health system. This multifactorial condition results from a chronically positive energy balance. In this context, achieving a negative energy balance is essential to address obesity, with recommendations that combine diet and physical exercise. Among the available dietary approaches, the ketogenic diet stands out for its high lipid intake and low carbohydrate intake. In addition, there is a scarcity of studies in the literature investigating the effects of diets with very low amounts of lipids and rich in carbohydrates. Given this scenario, the present study aimed to analyze the effects of ad libitum administration of a very low fat diet (VLF) compared to the ketogenic diet (KD), as well as its intermittent versions (IVLF and IKD), in C57BL/6 mice. The animals were fed their respective diets for 24 weeks. The intermittent groups alternated between the specific diet and the control diet. The glucose tolerance test was performed at week 23. Body composition, changes in glucose metabolism, and gene expression of glycolytic and lipolytic enzymes in liver, kidney, and muscle tissues were evaluated using the Real-Time Polymerase Chain Reaction technique. The results showed that the KD group reduced the percentage of body fat from the 16th week, presenting significantly lower values at the 22nd week compared to the other groups (p < 0.05). In addition, the expression of glucose transporter 2 was lower in relation to Ctrl (p = 0.0327) and VLF (p = 0.0128). The expression of Stearoyl-CoA reductase 1 was also lower in the KD group compared to Ctrl (p = 0.0244). In contrast, the IKD group showed an increase in food intake and body fat percentage in weeks 17 to 19, in addition to elevated expression of Stearoyl CoA reductase 1 in relation to the KD group (p = 0.0279). Stearoyl-CoA reductase 1 was higher in the IVLF group than in the KD group (p=0.0196), and the expression of Acetyl-CoA carboxylase 1 was also higher in the IVLF group (p=0.0243). It is concluded that the ketogenic diet promotes weight loss and alters the gene expression of lipogenic enzymes. Weight gain in the IKD group suggests that difficulty in maintaining adherence to restrictive diets may lead to unwanted weight gain.